IDENTIFICATION OF FASCIOLA SPP. ISOLATED IN GOATS IN VIETNAM USING MOLECULAR MARKERS - Giang Thanh, Nguyễn Thị; Trung, Triệu Nguyên; Hòa, Lê Thanh (Vietnam Journal of Biotechnology, 2013)
Fasciola hepatica and Fasciola gigantica (Fasciolidae) are the two species which cause fascioliasis in ruminants and humans. The ruminant animals: buffaloes, cattle, goats, sheep are highly susceptible to Fasciola spp. maintaining a reservoir and playing the role of transmission to humans. In recent years in Vietnam, the prevalence of fascioliasis in animals is very high and numer of human cases infected with the liverfluke are dramatically increased. Genetic markers of mitochondrial cox1 (cytochrome c oxidase subunit 1) and nuclear ITS-2 (internal transcribed spacer 2) have been obtained and sequenced from the liverflukes collected from goats in order to evaluate the genetic variation in the Fasciola population in different hosts. The sequences obtained were comparatively analyzed with those taken from GenBank revealed that major portion of Fasciola spp from goats were identified as “pure” Fasciola gigantica; but some of them were intermediate forms as hybrids between F. hepatica (male) x F. gigantica (female). All of these forms coexist in the fluke population in Vietnam. The interspecific hybridization and back-crosing (introgression) detected in the fluke population in goats makes their molecular genetics more complicated. This is the first time to confirm the hybrid form of Fasciola and their genetic variation in goat in Vietnam and worldwide.